Docetaxel targets aggressive methylation profiles and serves as a radiosensitizer in high-risk meningiomas. Issue 3 (17th August 2022) - Youngblood, Mark W; Tran, Anh N; Wang, Wenxia; An, Shejuan; Scholtens, Denise; Zhang, Lyndsee; O'Shea, Kaitlyn; Pokorny, Jenny L; Magill, Stephen T; Sachdev, Sean; Lukas, Rimas V; Ahmed, Atique; et al.
Abstract: Background: Meningioma is the most common primary intracranial tumor in adults. A subset of these tumors recur and invade the brain, even after surgery and radiation, resulting in significant disability. There is currently no standard-of-care chemotherapy for meningiomas. As genomic DNA methylation profiling can prognostically stratify these lesions, we sought to determine whether any existing chemotherapies might be effective against meningiomas with high-risk methylation profiles. Methods: A previously published dataset of meningioma methylation profiles was used to screen for clinically significant CpG methylation events and associated cellular pathways. Based on these results, patient-derived meningioma cell lines were used to test candidate drugs in vitro and in vivo, including efficacy in conjunction with radiotherapy. Results: We identified 981 genes for which methylation of mapped CpG sites was related to progression-free survival in meningiomas. Associated molecular pathways were cross-referenced with FDA-approved cancer drugs, which nominated Docetaxel as a promising candidate for further preclinical analyses. Docetaxel arrested growth in 17 meningioma cell sources, representing all tumor grades, with a clinically favorable IC50 values ranging from 0.3 nM to 10.7 mM. The inhibitory effects of this medication scaled with tumor doubling time, with maximal benefit in fast-growing lesions. The combination of Docetaxel and radiation therapy increased markers of apoptosis and double-stranded DNA breaks, and extended the survival of mice engrafted with meningioma cells relative to either modality alone. Conclusions: Global patterns of DNA methylation may be informative for the selection of chemotherapies against meningiomas, and existing drugs may enhance radiation sensitivity in high-risk cases.